¿Es necesario probar el daño moral en materia laboral? Análisis de la Casación N°7687-2021/LIMA - Franco Chavez, David (2024)
The purpose of this research work is to analyze Cassation No. 133969-2019 regarding Case No. 00294-2016-0-3001-JR-LA-01. In this case, the Supreme Court of Justice ruled in favor of Mr. Guillermo Joyo Galván in his lawsuit against his employer, Unión de Concreteras S.A.C – Unicon, for wrongful dismissal, reinstatement, and compensation for damages. Mr. Joyo Galván was terminated from his position as a concrete pump operator after falling asleep during his work shift. As a starting point, we will review precedents, legal doctrine, and jurisprudence that influenced the majority decision of the Supreme Court judges regarding the cassation appeal. Additionally, we will examine the criteria that led Justice Malca to vote against overturning the lower court’s ruling. To do so, we must consider the principles governing labor relations, the obligations of both employers and employees regarding workplace safety and health, and the infractions that employees may commit during their duties, potentially leading to termination. After internalizing these concepts, we will determine whether we agree with the validity of the cassation appeal and assess whether the plaintiff’s dismissal was justified due to a serious offense or if it was disproportionate on the part of the employer.